some of the dimensions of the concept of self and their relationship to performance skills basketball game - Khalid, Mayada (Journal of Physical Education, 2019)
This section provided and the importance of research was to address the performance skills and its impact cannot be so clearly indispensable in learning and has also been addressing the psychological impact and its impact on the educational process is self-psychological factors that are personal to the student the right to self-important part of the personal have been addressed also to some dimensions of self - The research problem identified in the study after physical and accept self-reliance and their impact on the performance skills of the game of basketball to the students that the second phase of the basketball student exposure to many of the test approved by the same (the same). 1-2 target search - Identify the type of relationship between the physical and after the self-reliance and to accept their performance skills in basketball studied a sample of members of the search. 1-3 a R - The existence of a correlation between each of the moral self, after the physical and accept self and performance skills in basketball studied a sample of members of the search 1-4 areas of research Area of human 1-4-1: - the second stage students in the Department of Physical Education College of Basic Education / Mustansiriya University. 1-4-2 temporal area: 12 10 2008 through 20 10 2008. 1-4-3 spatial area: - out the internal core of the Faculty of Education, Department of Physical Education / Mustansiriya University. Part II Researcher addressed in this chapter the concept of self and self-concept in sport and the dimensions of self-concept and the basic steps to learn the motor skills of sports and played basketball and also similar studies. Part III Researcher used the descriptive approach, where the scanning method, the sample of research (25) where the form was distributed to the same search, and coherence between the same variables in the research (height. Weight. Age) and was also the extraction of consistency and honesty of the self-contained as well as the scale of this chapter on the experience and means of reconnaissance statistics. Part IV In this section the presentation of results, discussed and analyzed in order to achieve the goal of research and to impose Part V Through the results of her research researcher b (the conclusions of three) than 1 - after the physical self to the students of Department of Physical Education (Phase II) has given an indication in terms of moral and statistical study basketball. 2 - after that accept self-education students in the sports department (second phase) has given an indication in terms of moral and statistical study basketball. As well as emerging researcher b (three recommendations) 1 -. Need to pay attention to the development of personality of students in all its many aspects from the understanding of the nature of the changes incurred by the stages of life and its impact on their perception of themselves and appreciation. 2 - to focus on the psychological aspects of both an end in the numbers of students and instilling in them confidence in themselves and rely on themselves to form themselves properly. 3 - to attempt to contribute to professional psychologists in the psychological preparation of students along with the numbers of the skills of trainers